TRANSPORMASI NILAI KEARIFAN LOKAL DIKILI DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI SD NEGERI 2 BULAWA KABUPATEN BONE BOLAGO - Estelin Yantu; Rahmatiah; Ramli Mahmud (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
This study explores how the transformation of Dikili’s local wisdom supports character development among students at SDN 2 Bulawa. Using a qualitative descriptive approach, it focuses on three aspects of moral growth: moral knowing, feeling, and action. Moral knowing is developed through religious and social values taught during morning zikir sessions, emphasizing love for the Prophet, sincerity, and sharing. Moral feeling emerges from students’ involvement in preparing tolangga for the Dikili procession, fostering solidarity and cooperation. Moral action is seen in students’ behavior—actively joining Dikili activities, helping peers, keeping their environment clean, and showing respect to teachers. The study concludes that integrating Dikili traditions plays a key role in shaping students’ moral understanding, emotional awareness, and ethical behavior.